“We Hold These Truths to Be Self-Evident”: Constitutionalism, Public Reason, and Legitimate Authority - Mattias Kumm (Public Reason and Courts, 2020)
Mattias Kumm puts forward the basic structure of an argument for a normative theory of public reason–based constitutionalism to determine what it would require if the law has the authority it claims to have but only if it is justifiable in terms of public reason and if constitutions seek to constitutionalize as a condition for legal validity this standard. Kumm contrasts public reason–based understandings of constitutionalism with conventionalist and democratic voluntarist conceptions of constitutionalism. He then discusses what a public reason–based understanding of constitutionalism implies for the foundations, structure, and interpretation of constitutions. Kumm concludes that even though the demands for establishing legitimate authority within a public reason–based framework are ambitious, public reason–based constitutionalism is the heir of the American and French revolutions, and dominant structures of prevailing constitutional practice in liberal democracies can be best explained and justified within such a framework.
Keywords: 300; constitutionalism; public reason; legitimacy